Progress in the compilation of an oxovanada-silsesquioxane portfolio and catalytic activity of organometallic representatives in ethylene polymerisation - Ohde, Christian; Limberg, Christian; Schmidt, Dennis; Enders, Markus; Demeshko, Serhiy; Knispel, Christina (Zeitschrift für anorganische und allgemeine Chemie, 2010)
Employing various incompletely condensed silsesquioxanes as ligand precursors in reactions with simple oxovanadates a variety of oxovanadium silsequioxanes could be synthesised, that might be regarded as models for oxovanadium units on silica surfaces. These include a tetranuclear vanadium(IV) compound as well as two complexes where O2V+ units are coordinated to two siloxide functions as part of a silsesquioxane framework. Moreover, compounds containing Cp*V(O)2+ moieties were prepared, whose activities as polymerisation procatalysts were examined: They turned out to be moderately active for the polymerisation of ethylene. All compounds were fully characterised, in case of the tetranuclear vanadium(IV) complex this also includes the investigation of the magnetic behaviour. Moreover, for two complexes also the molecular structures could be determined with sufficient quality by X-ray diffraction.